Atmospheric Architectures: The Aesthetics of Felt Spaces. Gernot Böhme. Edited/translated by A-C. Engels-Schwarzpaul - Hale, Jonathan (Interstices: Journal of Architecture and Related Arts, 2017)
BOOK REVIEW